Health Service Accessibility As A Key Predictor of Antenatal Care (K4 and K6) Completion in Low-Coverage Regions: A Cross-Sectional Study in Central Papua and North Maluku (SKI 2023) - Muhammad Irsyad Sabili; Sitti Raodhah; Habibi Habibi (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2026)
Maternal health is a key indicator of public health service quality. However, data from the 2023 Indonesian Health Survey (Survei Kesehatan Indonesia/SKI) indicate low coverage, with K4 coverage at 13.9% in Central Papua Province and K6 coverage of 4.1% in North Maluku Province. This study aimed to analyze individual and health service factors associated with pregnant women’s participation in ANC K4 and K6 visits in low-coverage areas. This quantitative observational study employed a cross-sectional design using secondary data from the 2023 Indonesian Health Survey. The study population consisted of women aged 10–54 years who had experienced pregnancy within the last year, with 118 respondents meeting the inclusion criteria. Data were analyzed using univariate, bivariate (Chi-square and Fisher’s Exact tests), and multivariate logistic regression. Most respondents were of low-risk reproductive age, with lower education in Central Papua. The majority had low gravida and parity, inadequate knowledge, and suboptimal iron supplementation. Many ANC services were provided by non-standard providers, and ANC participation remained low, especially in Central Papua. Bivariate analysis showed that in North Maluku Province, ANC participation was significantly associated with maternal age, type of pregnancy examiner, knowledge of pregnancy danger signs, iron supplementation consumption, and service accessibility (p < 0.05). In Central Papua Province, only maternal age was significantly associated (p < 0.05). Multivariate analysis identified service accessibility as the only significant factor in North Maluku (p = 0.020; Exp(B) = 0.088). Improving service accessibility and maternal health education is essential to increase ANC utilization in low-coverage areas.